(untitled) (Eurasian Research Bulletin, 2021)
This scientific work examines the issues associated with the problem of lack of financial resources, which is the need for sustainable economic growth. Based on the methods of Monica Kirya, financial problems in undeveloped as well as in more economically stable countries were examined and compared with each other.